CLIMATE CHANGE THREATS ON INDIGENOUS PREVENTIVE MEDICINE AND INITIATIVES FOR THE SPECIES’ CONSERVATION IN LIMPOPO PROVINCE, SOUTH AFRICA - Sejabaledi Agnes Rankoana (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Indigenous  plants  are  significant  sources  of  medicines  used  to  address  basic  health  carerequirements. Most significantly, the medicine is utilised as a preventative measure. Disease susceptibility is reduced by administering native plant products. Recent years have seen a decline in the number of indigenous plants gathered for preventative medicine due to the negative effects of drought and altered temperature patterns. The current research examined the state of indigenous plants used to make preventative medicine, the possible effects of climate change on the species, and traditional techniques employed to preserve the species for future usage. One hundred and six participants reported that they have knowledge of preventive care, which is accomplished through the administration of indigenous plant-derived remedies. Preventive amulets and salves are created from the roots, leaves, bulbs, bark, and stalks. Unfortunately, some plant species are endangered or extinct as a consequence of drought and rising temperatures. Participants demonstrated that they continue to use traditional conservation strategies to ensure the survival of rare species. This research recommends that the plant species identified by participants be added to the IUCN Red List in order to ensure their continued availability and usage in preventative care.